2007
DOI: 10.1016/j.neuron.2007.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Early Brain Development in Autism

Abstract: Although the neurobiology of autism has been studied for more than two decades, the majority of these studies have examined brain structure 10, 20, or more years after the onset of clinical symptoms. The pathological biology that causes autism remains unknown, but its signature is likely to be most evident during the first years of life when clinical symptoms are emerging. This review highlights neurobiological findings during the first years of life and emphasizes early brain overgrowth as a key factor in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
586
1
16

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 737 publications
(640 citation statements)
references
References 135 publications
37
586
1
16
Order By: Relevance
“…Several lines of evidence indicated that the rodent anterior frontal cortex (AFC) may be defective in ASD mouse models. First, studies in patients with ASD indicated dysfunction and early postnatal overgrowth in the frontal cortex 38 . Second, pyramidal neurons in the AFC showed hyperconnectivity in an ASD mouse model 39 .…”
Section: Resultsmentioning
confidence: 99%
“…Several lines of evidence indicated that the rodent anterior frontal cortex (AFC) may be defective in ASD mouse models. First, studies in patients with ASD indicated dysfunction and early postnatal overgrowth in the frontal cortex 38 . Second, pyramidal neurons in the AFC showed hyperconnectivity in an ASD mouse model 39 .…”
Section: Resultsmentioning
confidence: 99%
“…The computational results in this experiment demonstrate that overgrowth of the cortex will increase the cortical folding and convolution. This simulation result might provide theoretical clues to the following two independent studies: 1) In a MRI study of Autism, it was reported that the left frontal cortical folding is significantly increased in autism patient, but there is also a significant decrease in the frontal folding patterns with age in the autistic group [13]; and 2) It was reported that in Autism, the brain overgrows at the beginning of life and slows or arrests growth during early childhood [14]. In the future, it would be very interesting to combine our folding simulation studies with longitudinal MRI studies of Autistic brains and normal controls to further elucidate the relationship between brain growth and cortical folding in both Autism and normal neurodevelopment.…”
Section: Resultsmentioning
confidence: 81%
“…Sacco et al [55] investigated the clinical, morphological, and biochemical correlates of head circumference in autistic patients. Head growth rates are often accelerated in autism, especially in the first years of life [92]. Fronto-occipital head circumference was measured in 241 non-syndromic autistic patients, 3-16 years old.…”
Section: Our Roadmap: Methodological Issues and Strategiesmentioning
confidence: 99%
“…(iii) Head circumference is normal or even a little below the 50th percentile at birth; head overgrowth occurs between 1 and 7 years of age [92], possibly due to enhanced extracellular fluids in the deep gray matter/superficial white matter of the neocortex [96]. After 78 years of age, head growth slows down to below normal; (iv) ASD is a systemic disorder, with many patients displaying macrosomy [55], gastrointestinal symptoms [11], and immune abnormalities [10,97];…”
Section: Conclusion: Clinical and Research Perspectivesmentioning
confidence: 99%